Analytical methods for (oxidized) plasmalogens: Methodological aspects and applications. (May 2015) - Fuchs, B.
Abstract Plasmalogens are a unique class of glycerophospholipids (GPLs) containing a fatty alcohol linked by a vinyl-ether moiety at the sn-1 position of the glycerol backbone. There is normally a polyunsaturated fatty acyl residue at the sn-2 position. These two features provide interesting properties to the plasmalogen GPL. Their physiological roles have been challenging to elucidate, although plasmalogens represent up to 20% of the total membrane GPLs in humans. Recent studies have revealed plasmalogen deficiencies associated with several human disorders; therefore, plasmalogens are likely to be specific to different tissues, metabolic processes, and developmental stages. The first chapter of this review will discuss the molecular structure and chemistry of plasmalogens, their biological roles, and their distributions in cells and tissues in different species. In the second chapter, currently used methods of analyzing plasmalogens and their degradation products are described. Although chromatographic methods will be also discussed, special attention will be given to (31P) nuclear magnetic resonance spectroscopy and soft ionization mass spectrometry (MS) techniques such as electrospray ionization and matrix-assisted laser desorption and ionization time-of-flight MS. Finally, in the third chapter of this review selected human diseases and disorders, which are presumably characterized by changes in plasmalogen contents and compositions, are described and the analytical methods used are discussed.